2003
DOI: 10.1124/jpet.103.051938
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity, DNA Damage, and Apoptosis Induced by New Fotemustine Analogs on Human Melanoma Cells in Relation to O6-Methylguanine DNA-Methyltransferase Expression

Abstract: Fotemustine is a third generation chloroethylnitrosourea that has demonstrated significant antitumoral effects in malignant melanoma. However, its use is somewhat limited by its toxic side effects and chemoresistance caused by direct repair of O 6 -alkyl groups by the enzyme O 6 -methylguanine DNA-methyltransferase (MGMT). The aim of this work was to determine to what extent the expression of MGMT influences cytotoxicity, DNA damage, and apoptosis induced by new nitrososulfamide analogs of fotemustine (compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 33 publications
(43 reference statements)
2
21
0
Order By: Relevance
“…O6 -BG (5 µ M ) was used to try to deplete MGMT in the MGMT-transfected glioma lines; however, neither SNB19M nor U373M cells were sensitized to TMZ by O6 -BG, even when concentrations of O6 -BG were raised to 100 µ M . These cells continuously produce extremely high levels of MGMT protein, and sufficient concentrations of O6 -BG could not be achieved to deplete transfected cells of enzyme activity [30]. …”
Section: Resultsmentioning
confidence: 99%
“…O6 -BG (5 µ M ) was used to try to deplete MGMT in the MGMT-transfected glioma lines; however, neither SNB19M nor U373M cells were sensitized to TMZ by O6 -BG, even when concentrations of O6 -BG were raised to 100 µ M . These cells continuously produce extremely high levels of MGMT protein, and sufficient concentrations of O6 -BG could not be achieved to deplete transfected cells of enzyme activity [30]. …”
Section: Resultsmentioning
confidence: 99%
“…In a recent study it was reported that TMZ does not induce apoptosis, but senescence in human melanoma cells (Mhaidat et al, 2007), which is surprising in view of the fact that other cell systems such as malignant gliomas undergo apoptosis very efficiently in response to TMZ (Roos et al, 2007a). For fotemustine, it has been shown that melanoma cells are killed by apoptosis (Passagne et al, 2003;Kissel et al, 2006), but detailed studies on the mode of cell death by this drug in melanoma cells are not available. Also, there is no systematic study (utilising the same cell model) for melanomas as to the role of MGMT, p53, and MMR proteins in the O 6 -alkylguanine-triggered killing response.…”
mentioning
confidence: 99%
“…These cells are among the very radio-resistant in melanomas with a surviving fraction of 0.93 at 2 Gy protons [18] . FM has been shown to have a significant inhibitory effect on other melanoma cell lines in vitro [27,28] . This drug has increased the radio-sensitivity of HTB140 melanoma cells [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Irradiation doses of 12 and 16 Gy are in the range of those used in proton therapy [18] . The time point of 48 h after treatment was appropriate for the analysis of the drug effects as well as for the evaluation of the pro-apoptotic ability of the different treatments [28,36] . FM has shown the best inhibitory effects on HTB140 melanoma cell viability and proliferation between 48 and 72 h [32] .…”
Section: Discussionmentioning
confidence: 99%